The Application of Wordwall Learning Media to Improve the Indonesian Language Learning Outcomes of Students with ADHD in Grade V of SDN 07 Sedoya (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder characterized by inattention, impulsivity, and hyperactivity, which can interfere with academic performance and social interaction if not managed effectively. Students with ADHD often experience difficulties in maintaining focus and regulating their behavior during learning activities. Therefore, teachers need to employ appropriate learning media that can support students’ self-regulation and inhibitory control. This classroom action research was conducted with four fifth-grade students at SDN 07 Sedoya who exhibited ADHD-related symptoms. Data were collected through tests, observations, and documentation, and analyzed using the Miles and Huberman model. After five learning cycles using Wordwall media, students showed measurable improvement in both attention regulation and academic outcomes. The findings revealed that the use of Wordwall media increased the average learning achievement of students with ADHD by 15% compared to the initial cycle, with 75% of them surpassing the minimum mastery criterion. Moreover, students demonstrated better inhibitory control, reduced impulsive behaviors, and improved persistence during learning tasks. These results indicate that interactive digital media such as Wordwall can effectively enhance self-regulation and learning performance among elementary students with ADHD.